Structural Behavior of CHS T-Joints Subjected to Static In-Plane Bending in Fire Conditions - Fung, Tat Ching (2016)
Fire resistance of steel joints is always a major concern in the designing of steel structures against extreme hazard. However, for Circular Hollow Section (CHS) joints in fire condition, little information is available, especially for T-joints. In order to get more insight into the static behaviour of CHS T-joint in elevated temperatures, experimental and numerical studies were conducted on selected T-joints subject to in-plane bending under elevated temperatures. The failure modes and ultimate strength of the joints subjected to different temperatures were investigated and compared to the corresponding joint at ambient condition. Within the range of investigated parameters, elevated temperature at 700oC was observed to reduce the joint strength to 22.1% compared to the corresponding joint at ambient temperature. Furthermore, it is observed that at high temperature, there was a change in the failure mode of the joints. Cracks formed around the center weld toes before the joints reached excessive deformation which subsequently affected the joint post-yield hardening performance. In order to understand the initiation of the cracks, a material test was performed. The fracture strains of the HAZ of the chord material beneath center weld at corresponding temperatures were determined. It is noted that the fracture strains were included in subsequent FE validation models. The verified FEA models were used to analyze the structural behaviour of CHS T-joints at elevated temperature such as strain, stress, load path and effect of fracture strains to gain an insight into the failure mechanism of the joints.